Pemakzulan Presiden di Negara Hukum - Diniyanto, Ayon (Jurnal Negara Hukum: Membangun Hukum Untuk Keadilan, 2024)
The issue of impeaching the President in Indonesia has sparked public debate, particularly due to allegations of the President’s interference in elections, labeled as “cawe-cawe.” The Constitution indeed provides for the impeachment of the President, prompting questions regarding the timing and circumstances under which impeachment can occur. Specifically, whether impeachment can happen before an election or at the end of the President’s term and whether election interference constitutes a constitutional violation warranting impeachment. This research aims to address these questions by examining legal rules and procedures for presidential impeachment in Indonesia, exploring how impeachment intersects with elections and the end of the presidential term from a constitutional perspective, and comparing presidential impeachment processes across various jurisdictions. This research uncovers several key findings using a doctrinal legal research approach with statutory, conceptual, case, historical, and comparative analyses. Firstly, while the Indonesian constitution provides guidelines for presidential impeachment, it lacks specific regulations concerning the actions of presidential candidates during elections. Consequently, impeaching the President before an election or at the end of the term remains an issue without explicit legal basis. Looking at experiences in other countries, there have been instances of presidents facing impeachment both before elections and at the end of their terms; however, they were not necessarily removed from office. In conclusion, the research highlights the absence of explicit and detailed regulations regarding presidential impeachment in Indonesia. Recommendations are made to the MPR, DPR, and President to enhance policies concerning presidential impeachment, ensuring clarity and effectiveness in the impeachment process. AbstrakIsu pemakzulan Presiden di Indonesia menggema dan menjadi perdebatan masyarakat. Alasannya, Presiden dianggap cawe-cawe dalam Pemilu. Konstitusi telah mengatur pemakzulan Presiden. Pertanyaannya, apakah pemakzulan Presiden dapat dilakukan menjelang Pemilu dan di akhir masa jabatan? Pertanyaan selanjutnya, apakah perbuatan Presiden cawe-cawe dalam Pemilu merupakan pelanggaran konstitusi yang dapat dimakzulkan? Apakah di negara lain juga pernah terjadi hal tersebut? Penelitian ini merumuskan masalah: (1) bagaimana aturan hukum dan prosedur pemakzulan presiden di Indonesia? (2) bagaimana pemakzulan Presiden saat menjelang Pemilu dan di akhir masa jabatan dari perspektif konstitusi? dan (3) bagaimana perbandingan pemakzulan Presiden di berbagai negara hukum? Penelitian ini penelitian hukum doktrinal dengan pendekatan perundang-undangan, konseptual, kasus, sejarah, dan perbandingan. Hasil penelitian ini mengemukakan, bahwa konstitusi Indonesia mengatur secara materil dan formil terkait pemakzulan Presiden. Namun, konstitusi belum mengatur tindakan cawe-cawe Presiden dalam Pemilu. Pemakzulan Presiden menjelang Pemilu dan di akhir masa jabatan, untuk saat ini sebatas isu. Melihat kondisi di negara lain, memang sudah ada Presiden dimakzulkan menjelang Pemilu dan di akhir masa jabatan. Namun hasilnya tidak diberhentikan sebagai Presiden. Penelitian ini menyimpulkan belum ada aturan materil dan formil secara eksplisit dan rinci tentang pemakzulan Presiden. Saran kepada MPR, DPR, dan Presiden untuk perbaiki kebijakan tentang pemakzulan Presiden.